2012
DOI: 10.1016/j.radonc.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

NTCP models for patient-rated xerostomia and sticky saliva after treatment with intensity modulated radiotherapy for head and neck cancer: The role of dosimetric and clinical factors

Abstract: The multivariable NTCP models presented in this paper can be used to predict patient-rated xerostomia and sticky saliva. The dose volume parameters included in the models can be used to further optimise IMRT treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 27 publications
5
159
4
Order By: Relevance
“…Most of the previous studies reported on anatomic and dosimetric changes of the PG. This trend of study can be explained by the fact that radiation dosimetric changes for PGs are associated with saliva reduction and xerostomia 29, 30, 31…”
Section: Discussionmentioning
confidence: 96%
“…Most of the previous studies reported on anatomic and dosimetric changes of the PG. This trend of study can be explained by the fact that radiation dosimetric changes for PGs are associated with saliva reduction and xerostomia 29, 30, 31…”
Section: Discussionmentioning
confidence: 96%
“…Variables with Pearson correlation coefficients !0.70 were combined into a single variable (mean dose) to avoid the problem of multicollinearity (24). The dosimetric variables for OM (mean and maximum dose) plus variables listed in Table 1 were used as inputs for multivariate logistic regression to predict g3OM.…”
Section: Discussionmentioning
confidence: 99%
“…This interest for PG changes during radiotherapy can be explained by the fact that radiation dose to the PGs was associated with reduced saliva production [69] and xerostomia [70,71].…”
Section: Parotid Glandmentioning
confidence: 99%